2003
DOI: 10.1002/joc.905
|View full text |Cite
|
Sign up to set email alerts
|

Sea‐surface temperature co‐variability in the Southern Atlantic and Indian Oceans and its connections with the atmospheric circulation in the Southern Hemisphere

Abstract: The relationship between sea-surface temperature (SST) inter-annual variability at the subtropical and midlatitudes of the southern Atlantic and Indian Oceans and its links with the atmospheric circulation in the Southern Hemisphere are investigated over the 1950-1999 period. Exploratory analysis using singular value decomposition and further investigations based on simple indices show that a large part of regional SST variability is common between the southwestern parts of both basins at subtropical and midla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
93
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(105 citation statements)
references
References 38 publications
10
93
1
1
Order By: Relevance
“…The explained variances are 21.2 and 19.8%, respectively. These patterns broadly coincide with those depicted in Fauchereau et al (2003). They exhibit a pressure distribution over the Atlantic Ocean which is similar to that of the Indian Ocean, including anomalies of opposite signs between the tropical and the subtropical-temperate latitudes.…”
Section: Precipitationsupporting
confidence: 81%
See 1 more Smart Citation
“…The explained variances are 21.2 and 19.8%, respectively. These patterns broadly coincide with those depicted in Fauchereau et al (2003). They exhibit a pressure distribution over the Atlantic Ocean which is similar to that of the Indian Ocean, including anomalies of opposite signs between the tropical and the subtropical-temperate latitudes.…”
Section: Precipitationsupporting
confidence: 81%
“…Monthly mean sea-level pressure (SLP), which is used as the independent variable in the statistical downscaling model, is from NCAR/NCEP reanalysis data for 1948 to 1999 (Kalnay et al 1996). NCEP SLP has been shown to be close to the GMSLP (Global Mean Sea Level Pressure) observed data from the Hadley Centre (Fauchereau et al 2003). In addition, we also use gridpoint precipitation and SLP data from the GCM.…”
mentioning
confidence: 88%
“…Behera and Yamagata (2001) first identified 57 this phenomenon in the southern Indian Ocean. Since then, several studies have shown the 58 existence of subtropical dipoles in the South Atlantic (Fauchereau et al 2003) and South 59…”
Section: Ummenhofer Et Al 2009 Cai and Cowan 2013) 50mentioning
confidence: 99%
“…Beyond increases in temperature, climate change in sub-Saharan Africa is expected to cause changes in rainfall intensity (Thomas et al 2007;Songok et al 2011a), increases in the incidence of extreme events such as droughts and floods (Richard et al 2001;Fauchereau et al 2003;New et al 2006;Niang et al 2014;Tschakert et al 2010), increases in desertification (Reich et al 2001), and alterations in certain disease vectors causing changes in the spatial and temporal transmission of infectious diseases (Hay et al 2002;Chen et al 2006). Expected impacts include shortened or disrupted growing seasons, reductions in the area suitable for agriculture, and declines in agricultural yields in many regions of subSaharan Africa (Niang et al 2014;Müller et al 2011;Sarr 2012).…”
Section: Introductionmentioning
confidence: 99%